2022
DOI: 10.1002/solr.202200907
|View full text |Cite
|
Sign up to set email alerts
|

Red‐Light‐Driven CO2Photoreduction into CH4and CO Enabled by Narrow‐Gap Conjugated Microporous Polymers

Abstract: Herein, selective CO2 photoreduction into CH4 and CO with red light using conjugated microporous polymers (CMPs) at room temperature is reported. By incorporating electron‐rich pyrene and electron‐deficient fluorenone derivatives in the polymer networks to constructing intramolecular donor–acceptor system, the resulting three polymers show very broad light absorption covered from 350 to 1000 nm, with narrow gaps of 1.61–1.74 eV. In the presence of triethanolamine and 1‐benzyl‐1,4‐dihydronicotinamide as the sac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…To our knowledge, rare examples have been conducted for photocatalytic CO 2 reduction without any metal involvement. For this reason, it is highly desirable to use organic π-conjugated polymers, especially CMPs, as photocatalysts for metal-free photocatalytic CO 2 -to-CH 4 conversion, but thus far, only a few studies have been conducted. , For instance, Maji and co-workers reported that the donor–acceptor-based redox-active CMP with electron delocalization channel as a metal-free photocatalyst exhibited an impressive activity of CO 2 reduction to produce CH 4 with high generation rate and selectivity. Undoubtedly, the research of metal-free photocatalytic CO 2 -to-CH 4 conversion is still in its infancy, and rational designing of abundant yet unique catalytic sites in CMPs to improve the selectivity control of CH 4 versus other C 1 products is largely underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, rare examples have been conducted for photocatalytic CO 2 reduction without any metal involvement. For this reason, it is highly desirable to use organic π-conjugated polymers, especially CMPs, as photocatalysts for metal-free photocatalytic CO 2 -to-CH 4 conversion, but thus far, only a few studies have been conducted. , For instance, Maji and co-workers reported that the donor–acceptor-based redox-active CMP with electron delocalization channel as a metal-free photocatalyst exhibited an impressive activity of CO 2 reduction to produce CH 4 with high generation rate and selectivity. Undoubtedly, the research of metal-free photocatalytic CO 2 -to-CH 4 conversion is still in its infancy, and rational designing of abundant yet unique catalytic sites in CMPs to improve the selectivity control of CH 4 versus other C 1 products is largely underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…were generally substituted for water as electron donors to rapidly annihilate photogenerated holes to facilitate the efficient utilization of photogenerated electrons in CO 2 reduction. [18][19][20][21][22][23][24] However, this strategy not only wastes the energy of photogenerated holes, but the employment of high-cost sacrificial agents also significantly reduces the economic efficiency of the system. [25] To get rid of this dilemma, coupling CO 2 photoreduction and organic synthesis, that is, harnessing photogenerated holes to trigger valuable organic reactions, offers a win-win strategy for ameliorating the economic efficiency of photocatalytic CO 2 reduction.…”
Section: Introductionmentioning
confidence: 99%
“…were generally substituted for water as electron donors to rapidly annihilate photogenerated holes to facilitate the efficient utilization of photogenerated electrons in CO 2 reduction. [ 18–24 ] However, this strategy not only wastes the energy of photogenerated holes, but the employment of high‐cost sacrificial agents also significantly reduces the economic efficiency of the system. [ 25 ]…”
Section: Introductionmentioning
confidence: 99%
“…Fluorene is selected as a comonomer because of its inherent advantages of facile preparation and rigid planar structure for effective charge transport. 28,29 Under visible light (>420 nm) and in an atmosphere of water vapor, TEB-Flu with a surface area of 486 m 2 g −1 exhibited a CO generation rate of 40.4 μmol h −1 g −1 and ∼100% selectivity. By introducing 1,3,5-triphenylbenzene as a more extended core, the CO production rate of TPB-Flu could be greatly boosted to 83.1 μmol h −1 g −1 , due to the reduced optical gap, improved CO 2 adsorption and charge migration during the photocatalytic process.…”
Section: Introductionmentioning
confidence: 99%